Research Progress on Photosensitizers for DSSC - Carella, Antonio; Borbone, Fabio; Centore, Roberto (Frontiers in Chemistry, 2018)
Dye sensitized solar cells (DSSC) are considered one of the most promising photovoltaics technologies alternative to the traditional silicon based solar cells because of their compatibility with low cost manufacture methodologies, their peculiar optical and mechanical properties and their high indoor efficiency. Photosensitizers represent one of the most important part in a DSSC device and probably the most thoroughly investigated in the last twenty years, with thousands of dyes that have been proposed and tested for this kind of application. In this review we aimed to give an overview of the three main classes of DSSC photosensitizers, namely ruthenium (II) polypyridyl complexes, Zn-porphyrin derivatives and metal free organic dyes. After a brief introduction on the architecture and operational principles of a DSSC and on the state of the art of the other main components of this kind of device, we focused our discussion on photosensitizers. We defined the several requirements DSSC photosensitizers should fulfil and provided an excursus about their historical development along the years; by examining specific dyes reported in the literatures, we attempted to highlight the molecular design strategies that have been established for the optimization of their performance in actual devices both for what concerns efficiency (that recently reaches an outstanding 14.3 %) and operational stability. We finally discussed, in the last section, about the possible future developments of this intriguing technology.